2002
DOI: 10.1034/j.1600-0668.2002.120102.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High Endotoxin Concentrations in the Settled Dust of German Homes

Abstract: Endotoxin concentrations in settled house dust were measured within the collaborative study named INGA (Indoor Exposure and Genetics in Asthma) together with other asthma-related indoor factors in 405 randomly selected homes in two German cities. Endotoxin was assayed using the quantitative kinetic chromogenic Limulus Amebocyte Lysate (LAL) method. The mean concentration of 2,274 ng endotoxin/g dust in living rooms is about two orders of magnitude below mean occupational exposure (e.g. agriculture). Endotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
5
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 1 publication
16
102
5
1
Order By: Relevance
“…In NYC, differences in endotoxin among the neighborhoods may reflect the differences in housing stock. Unlike a German study, we did not find any associations with the story of the apartment (30). The same German study also reported higher endotoxin in older buildings (before 1980).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In NYC, differences in endotoxin among the neighborhoods may reflect the differences in housing stock. Unlike a German study, we did not find any associations with the story of the apartment (30). The same German study also reported higher endotoxin in older buildings (before 1980).…”
Section: Discussioncontrasting
confidence: 96%
“…These findings are in keeping with a German study (30) that found an association with mouse sightings and the U.S. National Home Survey that found an association with cockroach allergen (29). With regression analysis, mouse and cockroach allergens were found to be independently associated with endotoxin; however, these variables combined only explained 11% of the variation in endotoxin.…”
Section: Discussionsupporting
confidence: 88%
“…Results on biocontaminant levels of the first home visit of the INGA study have been published previously (Fahlbusch et al, 1999Koch et al, 2000;Heinrich et al, 2001;Bischof et al, 2002;Gro et al, 2001). Here we present the results on repeated measurements of biocontaminants collected in the same homes.…”
Section: Resultsmentioning
confidence: 89%
“…Endotoxin concentrations in living-room floor dust sampled in homes without pets and vermin were lower than those sampled in homes with pets or vermin [24]. Endotoxin concentrations were higher in old buildings and in the lower storey of the dwelling, and were associated with longer occupancy in the apartment, high utilisation of the apartment during the sampling period, infrequent vacuum cleaning of the carpets, and an indifferent attitude to ventilation and keeping cats and dogs [25]. Summarising the results of comparative indoor measurements in Erfurt and Hamburg, it was concluded that despite detected regional differences, these differences probably only contribute a little to the different prevalences in atopic outcomes.…”
mentioning
confidence: 79%